The Myth of the God Fish in Monte's Hair Pond as a Conservation Narrative - Sevira; Eti Setiawati (Universitas Negeri Semarang, 2025)
This research aims to explore and examine the meaning of the mythical narrative of the God Fish in the Monte Hair Lake as part of efforts to conserve endemic animals and preserve their habitats. Oral literature in the form of myths in the region is examined and scrutinized in order to find values that are full of the call to protect nature and the living things that exist in it. This study uses a qualitative approach through narrative analysis as a method, with Roland Barthes' semiotic theory and Durkheim's theory of belief as the basis of the analysis. The data used were in the form of oral speech, phenomena, and behaviors that had indications related to animal conservation efforts and literature review. The data sources in the study were the key interpreters and the community around the lake in the form of data in the form of oral narrative speech. Structured interview techniques and literature review collected data. Based on the research that has been carried out, the findings in this study show several forms of myths spread in the region, including that the God Fish is told as the incarnation of a royal warrior, cannot be consumed, has luck, and is sacred. The existence of myths in the Monte Hair area has a function to strengthen collective awareness to maintain the existence of the God Fish as a 'protector' of the local aquatic ecosystem of the Monte Hair Lake.